THE EFFECT OF HEALTH EDUCATION AUDIOVISUAL BASED ON HEALTH BELIEF MODEL TOWARDS COMPLIANCE BEHAVIOR OF TB PATIENTS IN PREVENTION TRANSMISSION AT NAMBO PUBLIC HEALTH CENTER AREA: HEALTH EDUCATION - Nofitasari, Ari; Nawawi; Mimi Yati; Sarah Sarizan Yunam (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2020)
Background: Health education can improve an adherence and reduce treatment delays in Tuberculosis (TB) patients. Based on results of interviews with TB patients at Nambo Public Health Center in December 2019, the results of interviews that has conducted on 4 patients, it found that the patients was undergoing treatment at the public health center , there were family members who were undergoing same treatment, there had been no routine preventive measures. The 4 patients interviewed said that they did not know clearlyto preventiontransmissionÂ  because the health worker only gave a sheet of paper which was recommended to be read at home. The General objective of this study was to determine the effect of health education patients in prevention of transmission at the Nambo Public Health Center Area. Methods: The type of study was quasyi experimental method with a pre test and post test design. The population of this study was 75 people, by using proportional random sampling technique with 26 respondents. The method of analysisÂ  used paired t test of the statistical analysis. Result: The results of this study, showed that the above table analysis obtained the value of t=10,111>1,706, where t count was greater than the value of t table. It shows that there was asignificant effect of Health Prevention behavior at Nambo Public Health Center. Conclusion: It is hoped that the Nambo Community Health Center will always educationorconselingwhichwillincreasecommunityknowledge on TB prevention in the working area.